A processing technology and product for improving high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy
After the nickel-based alloy is manufactured through powder bed laser melt additive, combined with solid solution treatment, laser impact strengthening, intermediate heat treatment and shot peening strengthening processes, LSP+HT+SP alloys are formed, which solves the problem of insufficient high-temperature fatigue performance of nickel-based alloys and significantly improves its high-temperature fatigue life.
Patent Information
- Application Number
- CN202410111037.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-01-26
AI Technical Summary
High-temperature fatigue fracture is the main form of in-service failure of nickel-based alloy components, especially in laser additive manufacturing alloys, metallurgical defects such as pores and unfusion and high surface roughness, resulting in insufficient fatigue performance.
After using powder bed laser melt additive manufacturing technology, solid solution treatment is carried out, grinding is used to remove the oxide layer, followed by double-sided laser impact strengthening, intermediate heat treatment and double-sided shot peening strengthening to form an LSP+HT+SP alloy.
Through this process, the high-temperature fatigue performance of nickel-based alloys is significantly improved, and the high-temperature fatigue life of the aging-strengthening nickel-based alloys is significantly better than that of a single reinforced alloy.
Smart Images

Figure CN117884650B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high-temperature alloy additive manufacturing, and in particular relates to a processing technology and a product thereof for improving the high-temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloys. Background Art
[0002] Age-hardened nickel-based superalloys have excellent mechanical properties due to the dispersion of precipitation strengthening phases such as γ′ and γ″, and are widely used in aerospace and other fields. Laser additive manufacturing technology provides greater design freedom for near-net-shape nickel-based alloy complex structural parts, effectively reduces the waste of expensive raw materials, and greatly shortens the processing steps and cycles. Therefore, it has great application prospects in aerospace and other fields. However, high-temperature fatigue fracture is still the main form of in-service failure of nickel-based alloy components, especially in laser additively manufactured alloys, where there are metallurgical defects such as pores and unfused metallurgical defects, high surface roughness and residual tensile stress, which are unfavorable factors that easily induce crack initiation and propagation. Therefore, improving high-temperature fatigue performance has become a key issue that needs to be urgently solved for high-performance laser additively manufactured nickel-based superalloy components.
[0003] Although heat treatment is an important post-processing step for additively manufactured nickel-based alloys to release residual tensile stress and regulate anisotropic microstructure and properties, it can only eliminate ~70% of residual tensile stress, and has great limitations in improving fatigue performance. Hot isostatic pressing is another common additive manufacturing post-processing process. Although it can effectively reduce the number and size of pores inside nickel-based alloy specimens, it is easy to cause the dissolution of the γ″ strengthening phase, resulting in a decrease in the yield strength of the material, and the improvement of fatigue performance is very limited. In recent years, surface deformation strengthening methods such as mechanical shot peening (SP), laser shock strengthening (LSP), and ultrasonic shot peening have gradually gained widespread attention in the anti-fatigue post-processing of additively manufactured nickel-based alloys by introducing residual compressive stress in the near-surface layer of the alloy and improving the surface roughness and near-surface microstructure to a certain extent. However, conventional surface deformation strengthening methods still generally have the problem of poor thermal stability of the strengthening layer structure and stress, resulting in insufficient improvement in the high-temperature fatigue performance of the alloy.
[0004] Therefore, how to provide a method that can effectively improve the high temperature fatigue performance of the alloy is a technical problem that those skilled in the art urgently need to solve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a processing technology and a product thereof for improving the high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloys.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A processing technology for improving the high temperature fatigue performance of an additively manufactured aging-strengthened nickel-based alloy comprises the following steps:
[0008] The nickel-based alloy powder is formed by powder bed laser melting additive manufacturing technology and then subjected to solid solution treatment. After polishing to remove the oxide layer, it is sequentially subjected to double-sided laser shock strengthening treatment, intermediate heat treatment and double-sided shot peening strengthening treatment to obtain the LSP+HT+SP alloy.
[0009] Beneficial effects: The typical heat treatment system of the additively manufactured aging-strengthened nickel-based alloy in the present invention is solution-aging treatment. The main purpose of solution treatment is to eliminate organizational anisotropy and Nb element segregation, and promote the dissolution of hard and brittle Laves phase in the matrix phase, while aging heat treatment is to precipitate γ′ and γ″ nano-strengthening phases and improve the strength of the alloy. However, compared with solution-aging alloys, due to the lack of strengthening phases in the solution alloy, the plastic deformation degree of the surface and near-surface layer is more significant during double-sided laser shock strengthening treatment, and the dislocation density is higher. Therefore, in the aging heat treatment after strengthening (i.e., intermediate heat treatment), it is more conducive to promoting the precipitation of nano-strengthening phases, thereby improving the pinning effect of nano-strengthening phases on dislocations, improving the thermal relaxation behavior of residual compressive stress, and improving the high-temperature fatigue performance of the alloy. However, Since the heat input of aging heat treatment will inevitably lead to thermal relaxation of some residual stress, it is necessary to perform a surface deformation strengthening treatment after heat treatment. Laser shock strengthening (LSP) and shot peening (SP) are two commonly used surface deformation strengthening methods for aviation materials. The thickness of the residual compressive stress action layer of the former is much greater than that of the latter due to the ultra-high strain rate, but the induced residual compressive stress value is not as significant as the latter. Therefore, through the LSP+SP composite, the advantages of the two single strengthening methods can be combined, so that the additively manufactured aging-strengthened nickel-based alloy has a thicker residual compressive stress layer and a work hardening layer and a higher surface residual stress value, so that the high-temperature fatigue life of the composite-strengthened alloy is significantly better than that of the single-strengthened alloy. Therefore, double-sided shot peening strengthening treatment is carried out after the intermediate heat treatment.
[0010] Preferably, the nickel-based alloy powder is prepared by vacuum induction melting and inert gas atomization;
[0011] The sum of the contents of impurity elements such as oxygen, nitrogen, and hydrogen in the nickel-based alloy powder does not exceed 150 ppm.
[0012] Beneficial effects: The present invention controls the content of impurity elements such as oxygen, nitrogen, hydrogen, etc. in the alloy powder to avoid the impurity elements from deteriorating the mechanical properties of the alloy, especially the high-temperature mechanical properties.
[0013] Preferably, the powder bed laser melting additive manufacturing technology is a laser selective melting technology;
[0014] Among them, the laser power is 200-210W, the scanning speed is 1520-1600mm / s, the scanning interval is 58-62μm, and the powder layer thickness is 28-32μm.
[0015] Beneficial effect: The present invention suppresses the formation of metallurgical defects such as pores and unfused alloys by adopting the above-mentioned laser additive manufacturing process parameters, improves the density inside the alloy, and thus obtains good fatigue performance.
[0016] Preferably, the temperature of the solution treatment is 1080-1100° C. and the time is 1-2 hours.
[0017] Preferably, the grinding is performed until the surface roughness Ra≤0.8 μm.
[0018] Beneficial effect: The present invention removes the oxide film formed on the surface of the alloy during the solution treatment process by grinding, and reduces the surface roughness to a lower level, thereby avoiding deterioration of the fatigue performance of the alloy due to high surface roughness.
[0019] Preferably, the laser energy density of the laser shock peening is 6 to 10 GW / cm 2 .
[0020] Beneficial effect: The present invention adopts the above-mentioned laser shock strengthening process parameters to cause significant plastic deformation on the surface of the solid solution additively manufactured aging-strengthened nickel-based alloy, forming a high-density dislocation zone and a thick residual compressive stress layer.
[0021] Preferably, the temperature of the intermediate heat treatment is 600-750°C, and the vacuum degree is ≤10 -2 Pa, time is 4 to 16 hours.
[0022] Beneficial effect: The present invention optimizes the intermediate heat treatment process to precipitate more nano-strengthening phases inside the LSP-strengthened additively manufactured aging-strengthened nickel-based alloy and pin dislocations, thereby improving the thermal stability of the microstructure and residual stress and improving the high-temperature fatigue performance of the alloy.
[0023] Preferably, the diameter of the shot peening treatment shot is 0.2-0.5 mm, the Almen strength is 0.1-0.2 mmA, and the coverage is ≥100%.
[0024] Beneficial effect: The present invention further strengthens the pinning effect of the nano-reinforced phase and dislocations on the alloy surface and near the surface through the preferred shot peening strengthening process, and forms high residual compressive stress on the alloy surface, so that the alloy has both a thick residual compressive stress layer and a high residual compressive stress value, further improving the fatigue performance of the alloy.
[0025] A LSP+HT+SP nickel-based alloy is prepared by a processing technology for improving the high-temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] The present invention uses a new thermal synergistic surface strengthening process of LSP+SP surface composite deformation strengthening combined with intermediate heat treatment to regulate and improve the thermal stability of the alloy strengthening layer structure and stress, and improve the high-temperature fatigue performance of laser additively manufactured nickel-based alloys. First, LSP+SP composite strengthening combines the advantages of two single surface strengthening methods, so that the additively manufactured nickel-based alloy has a thicker residual compressive stress layer, a work hardening layer and a higher surface residual compressive stress value, which effectively improves the fatigue performance; secondly, the introduction of intermediate heat treatment between the two surface deformation strengthening processes of LSP and SP promotes the generation of high-density dislocations and the precipitation of nano-strengthening phases, and enhances the interaction between the precipitated phase and metastable defects such as dislocations and subgrains, thereby effectively improving the thermal stability of the structure and stress of the alloy strengthening layer, and significantly improving the high-temperature fatigue performance of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0029] Figure 1 A processing flow chart provided by the present invention;
[0030] Figure 2 The pinning phenomenon between the nano-precipitated strengthening phase and the high-density dislocations in the strengthening layer of the LSP+HT+SP alloy obtained in Example 1 was observed by transmission electron microscopy;
[0031] Figure 3 Schematic diagram of the structure of the additively manufactured fatigue specimens and their surface deformation strengthening areas in Examples 1-2 and Comparative Examples 1-4 of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] The embodiment of the present invention provides a processing technology for improving the high temperature fatigue performance of an additively manufactured aging-strengthened nickel-based alloy, comprising the following steps:
[0035] The nickel-based alloy is formed by powder bed laser melting additive manufacturing technology and then subjected to solid solution treatment. After polishing to remove the oxide layer, it is sequentially subjected to double-sided laser shock strengthening treatment, intermediate heat treatment and double-sided shot peening strengthening treatment to obtain the LSP+HT+SP alloy.
[0036] In a preferred embodiment, the nickel-based alloy powder is prepared by vacuum induction melting and inert gas atomization;
[0037] The sum of the contents of impurity elements such as oxygen, nitrogen, and hydrogen in the nickel-based alloy powder does not exceed 150 ppm.
[0038] In a preferred embodiment, the powder bed laser melting additive manufacturing technology is a laser selective melting technology;
[0039] Among them, the laser power is 200-210W, the scanning speed is 1520-1600mm / s, the scanning interval is 58-62μm, and the powder layer thickness is 28-32μm.
[0040] In a preferred embodiment, the temperature of the solution treatment is 1080-1100° C. and the time is 1-2 hours.
[0041] In a preferred embodiment, the grinding is grinding to a surface roughness Ra≤0.8 μm.
[0042] In a preferred embodiment, the laser energy density of the laser shock peening is 6 to 10 GW / cm 2 .
[0043] In a preferred embodiment, the intermediate heat treatment temperature is 600-750°C and the vacuum degree is ≤10 -2 Pa, time is 4 to 16 hours.
[0044] In a preferred embodiment, the diameter of the shot peening treatment is 0.2-0.5 mm, the Almen intensity is 0.1-0.2 mmA, and the coverage is ≥100%.
[0045] The embodiment of the present invention also provides a LSP+HT+SP nickel-based alloy prepared by a processing technology for improving the high-temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy.
[0046] Example 1
[0047] A processing technology for improving the high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy, wherein the nickel alloy powder is GH4169 aging-strengthened nickel-based alloy powder prepared by vacuum induction melting inert gas atomization method, and the particle size distribution is: D 10 =20.01μm, D 50 =33.50μm, D 90 =54.08μm, impurity element content: O+N+H=98ppm, the processing technology specifically includes the following steps:
[0048] (1) Additive manufacturing: Nickel alloy powder is prepared by laser selective melting technology to obtain Figure 3 The as-deposited fatigue specimen shown in the figure has a laser power of 210 W, a scanning speed of 1580 mm / s, a scanning interval of 60 μm, and a powder layer thickness of 30 μm;
[0049] (2) Solution heat treatment: The as-deposited fatigue specimen obtained in step (1) was solution treated at 1080° C. for 1.5 h, and then polished to remove the surface oxide layer, and the surface roughness of the specimen was made Ra = 0.8 μm, to obtain a solid solution alloy with a smooth surface;
[0050] (3) Laser shock peening: The solid solution alloy obtained in step (2) is subjected to double-sided laser shock peening treatment, and the strengthening area is as follows: Figure 3 As shown in the dashed box, the laser energy density is 8GW / cm 2 , the spot diameter is 2.0 mm, the overlap rate is 50%, and the LSP strengthened alloy is obtained;
[0051] (4) Intermediate heat treatment: The LSP strengthened alloy obtained in step (3) is subjected to intermediate heat treatment in a high temperature vacuum furnace, wherein the vacuum degree is 8×10 -3 Pa, heat treatment temperature is 700℃, holding time is 10h, and LSP+HT alloy is obtained;
[0052] (5) Shot peening: The LSP+HT alloy obtained in step (4) is subjected to double-sided shot peening treatment. Figure 3 As shown in the dotted box, the Almen strength used is 0.15 mmA, the coverage is 100%, the projectile diameter is 0.4 mm, the material is alumina ceramic, and the LSP+HT+SP alloy is obtained.
[0053] The peak residual compressive stress of the LSP+HT+SP alloy was measured by a gradient residual stress instrument to be -1032MPa, and the thickness of the residual compressive stress layer was 726μm. The microstructure of the LSP+HT+SP alloy at a depth of 50μm near the surface was observed by transmission electron microscopy. Figure 2As shown in the figure, it can be seen that the nano-precipitation strengthening phase and the high-density dislocation (the geometric dislocation density is about 5.76×10 15 m -2 ) between the LSP+HT+SP alloy and the 1×10 7 No failure occurs after multiple pull-pull cycles.
[0054] Example 2
[0055] A processing technology for improving the high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy, wherein the nickel alloy powder is GH4169 aging-strengthened nickel-based alloy powder prepared by vacuum induction melting inert gas atomization method, and the particle size distribution is: D 10 =21.35μm, D 50 =33.68μm, D 90 =51.67μm, impurity element content: O+N+H=123ppm, the processing technology specifically includes the following steps:
[0056] (1) Additive manufacturing: Nickel alloy powder is prepared by laser selective melting technology. Figure 3 The as-deposited fatigue specimen shown in the figure has a laser power of 200 W, a scanning speed of 1600 mm / s, a scanning interval of 62 μm, and a powder layer thickness of 30 μm;
[0057] (2) Solution heat treatment: The as-deposited fatigue specimen obtained in step (1) was solution treated at 1100° C. for 1 h, and then polished to remove the surface oxide layer and make the surface roughness of the specimen Ra = 0.8 μm, thereby obtaining a solid solution alloy with a smooth surface;
[0058] (3) Laser shock peening: The solid solution alloy obtained in step (2) is subjected to double-sided laser shock peening treatment, and the strengthening area is as follows: Figure 3 The dashed box shows that the laser energy density used is 6 GW / cm 2 , the spot diameter is 2.0 mm, the overlap rate is 50%, and the LSP strengthened alloy is obtained;
[0059] (4) Intermediate heat treatment: The LSP strengthened alloy obtained in step (3) is subjected to intermediate heat treatment in a high temperature vacuum furnace, wherein the vacuum degree is 9×10 -3 Pa, heat treatment temperature is 600℃, holding time is 14h, and LSP+HT alloy is obtained;
[0060] (5) Shot peening: The LSP+HT alloy obtained in step (4) is subjected to double-sided shot peening treatment. Figure 3As shown in the dotted box, the Almen strength used is 0.1 mmA, the coverage is 100%, the projectile diameter is 0.3 mm, the material is alumina ceramic, and the LSP+HT+SP alloy is obtained.
[0061] The peak residual compressive stress of the LSP+HT+SP alloy was measured by a gradient residual stress instrument to be -804 MPa, and the thickness of the residual compressive stress layer was 715 μm. The geometric dislocation density in the microstructure at 50 μm near the surface of the alloy was about 4.32×10 15 m -2 There is an obvious pinning effect between the nano-strengthening phase and dislocations. When the temperature is 650℃ and the tensile stress level is 680MPa, the LSP+HT+SP alloy is subjected to 1×10 7 No failure occurs after multiple pull-pull cycles.
[0062] Comparative Example 1
[0063] A processing technology for improving the high temperature fatigue performance of additively manufactured aging-hardened nickel-based alloy, which is different from Example 1 only in that the order of the process steps is adjusted, and the intermediate heat treatment of step (4) and the laser shock strengthening of step (3) are interchanged. Specifically, the following steps are included:
[0064] (1) Additive manufacturing: Nickel alloy powder is prepared by laser selective melting technology to obtain Figure 3 The as-deposited fatigue specimen shown in the figure has a laser power of 210 W, a scanning speed of 1580 mm / s, a scanning interval of 60 μm, and a powder layer thickness of 30 μm;
[0065] (2) Solution heat treatment: The as-deposited fatigue specimen obtained in step (1) was solution treated at 1080° C. for 1.5 h, and then polished to remove the surface oxide layer, and the surface roughness of the specimen was made Ra = 0.8 μm, to obtain a solid solution alloy with a smooth surface;
[0066] (3) Intermediate heat treatment: The solid solution alloy obtained in step (2) is subjected to intermediate heat treatment in a high temperature vacuum furnace, wherein the vacuum degree is 8×10 -3 Pa, heat treatment temperature is 700℃, and holding time is 10h;
[0067] (4) Laser shock peening: The alloy obtained in step (3) is subjected to double-sided laser shock peening treatment, and the strengthening area is as follows: Figure 3 As shown in the dashed box, the laser energy density is 8GW / cm 2 , the spot diameter is 2.0mm, and the overlap rate is 50%;
[0068] (5) Shot peening: The alloy obtained in step (4) is subjected to double-sided shot peening treatment, and the strengthening area is as follows: Figure 3 As shown in the dotted box, the Almen strength used is 0.15 mmA, the coverage is 100%, the projectile diameter is 0.4 mm, the material is alumina ceramic, and a strengthened alloy is obtained.
[0069] The peak residual compressive stress of the strengthened alloy was measured by a gradient residual stress instrument to be -810 MPa, and the thickness of the residual compressive stress layer was 603 μm. The geometric dislocation density in the microstructure at 50 μm near the surface of the alloy was about 2.5×10 15 m -2 However, there is no obvious pinning phenomenon between the nano-strengthening phase and the dislocation. At a temperature of 650℃ and a tensile stress level of 680MPa, the tensile-tensile fatigue life of the strengthened alloy is 8.87×10 5 Second-rate.
[0070] Comparative Example 2
[0071] A processing technology for improving the high temperature fatigue performance of additively manufactured age-hardened nickel-based alloy, which is different from Example 1 only in that the intermediate heat treatment in step (4) is not included. The other steps and parameters are the same as those in Example 1.
[0072] The peak residual compressive stress of the strengthened alloy was measured by a gradient residual stress instrument to be -1015MPa, and the thickness of the residual compressive stress layer was 703μm. The geometric dislocation density in the microstructure at 50μm near the surface of the alloy was about 6.06×10 15 m -2 However, no obvious nano-strengthening phase was observed. At a temperature of 650°C and a tensile stress level of 680 MPa, the tensile-tensile fatigue life of the strengthened alloy was 1.03×10 5 Second-rate.
[0073] Comparative Example 3
[0074] A processing technology for improving the high temperature fatigue performance of additively manufactured age-hardened nickel-based alloy, which is different from Example 1 only in that the shot peening strengthening in step (5) is not included. The other steps and parameters are the same as those in Example 1.
[0075] The peak residual compressive stress of the strengthened alloy was measured by a gradient residual stress instrument to be -579 MPa, and the thickness of the residual compressive stress layer was 658 μm. The geometric dislocation density in the microstructure at 50 μm near the surface of the alloy was about 9.5×10 14 m -2 At a temperature of 650°C and a tensile stress level of 680 MPa, the tensile fatigue life of the strengthened alloy is 8.95×10 4 Second-rate.
[0076] Comparative Example 4
[0077] A processing technology for improving the high temperature fatigue performance of additively manufactured age-hardened nickel-based alloy, which is different from Example 1 only in that the laser shock strengthening in step (3) is not included. The other steps and parameters are the same as those in Example 1.
[0078] The peak residual compressive stress of the strengthened alloy was measured by a gradient residual stress instrument to be -638 MPa, and the thickness of the residual compressive stress layer was 452 μm. The geometric dislocation density in the microstructure at 50 μm near the surface of the alloy was about 1.7×10 15 m -2 , and there is no obvious pinning phenomenon between the nano-strengthening phase and the dislocation. At a temperature of 650℃ and a tensile stress level of 680MPa, the tensile-tensile fatigue life of the strengthened alloy is 6.13×10 5 Second-rate.
[0079] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A processing technology for improving the high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy, characterized in that: The following steps are involved: The nickel-based alloy powder is formed by powder bed laser melting additive manufacturing technology, then subjected to solution treatment, polished to remove the oxide layer, and then subjected to double-sided laser shock strengthening treatment, intermediate heat treatment and double-sided shot peening treatment in sequence to obtain LSP+HT+SP alloy; The powder bed laser melting additive manufacturing technology is a laser selective melting technology; Among them, the laser power is 200-210W, the scanning speed is 1520-1600mm / s, the scanning interval is 58-62μm, and the powder layer thickness is 28-32μm; The temperature of the solution treatment is 1080-1100°C and the time is 1-2h; The laser energy density of the laser shock peening is 6 to 10 GW / cm 2 ; The temperature of the intermediate heat treatment is 600-700°C, and the vacuum degree is ≤10 -2 Pa, time is 10-14h; The diameter of the shot peening treatment shot is 0.2-0.5 mm, the Almen intensity is 0.1-0.2 mmA, and the coverage is ≥100%.
2. A processing technology for improving high temperature fatigue performance of additively manufactured age-hardened nickel-based alloy according to claim 1, characterized in that: The nickel-based alloy powder is prepared by vacuum induction melting and inert gas atomization method; The sum of the contents of impurity elements such as oxygen, nitrogen, and hydrogen in the nickel-based alloy powder does not exceed 150 ppm.
3. A processing technology for improving high temperature fatigue performance of additively manufactured age-hardened nickel-based alloy according to claim 1, characterized in that: The grinding is performed until the surface roughness Ra is less than or equal to 0.8 μm.
4. The LSP+HT+SP nickel-based alloy prepared by the processing technology for improving the high temperature fatigue performance of additively manufactured aging-strengthened nickel-based alloy as described in claim 1.
Citation Information
Patent Citations
Heat treatment method for improving strength and plasticity of additive manufacturing nickel-based alloy thin-wall component
CN116673500A
Method for reducing hydrogen embrittlement sensitivity of nickel-based corrosion-resistant alloy
CN117187721A
Surface treatment of austenitic ni-fe-CR based alloys
WO2003046242A1
Cited By
Controlled electric arc additive and controllable deformation composite forming method and device
CN119457326A